2012
DOI: 10.4103/0974-2069.99610
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of clinical and Doppler echocardiographic findings in children and adolescents with significant rheumatic valvular disease

Abstract: Introduction:The diagnosis of acute rheumatic fever (RF) is based on clinical findings. However, during the chronic phase of the disease, the clinical approach is not sufficient for the follow-up of the patients and the Doppler echocardiography is a tool for the diagnosis of cardiac involvement. Prognostic variables that influence long-term outcomes are not well known.Methods:462 patients with RF according to Jones criteria were studied, and followed-up from the initial attack to 13.6 ± 4.6 years. All patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…In one study, the prevalence of subclinical carditis following the first episode of ARF was 18% and half of the patients had persistence or deterioration of disease 2–23 months later 178 . Studies by Araujo and colleagues 179 and Pekpak and colleagues 180 reported that the proportion of patients with subclinical ARF who had persistence of carditis at least 1 year later was 72% and 55%, respectively.…”
Section: Diagnosis Screening and Preventionmentioning
confidence: 99%
“…In one study, the prevalence of subclinical carditis following the first episode of ARF was 18% and half of the patients had persistence or deterioration of disease 2–23 months later 178 . Studies by Araujo and colleagues 179 and Pekpak and colleagues 180 reported that the proportion of patients with subclinical ARF who had persistence of carditis at least 1 year later was 72% and 55%, respectively.…”
Section: Diagnosis Screening and Preventionmentioning
confidence: 99%
“…In Brazil, 462 rheumatic patients were followed up for 13.6 years. More than one third of them presented recurrences by non-adherence to secondary prophylaxis ( 26 ).…”
Section: Discussionmentioning
confidence: 99%
“…198 In another study involving 258 children and adolescents with ARF followed up from 2 to 15 years, valve lesions healed in 25% of the patients with mild carditis, in 2.5% of those with moderate carditis, while no healing was observed in those with severe carditis. 199 • According to the GBD 2017, from 1990 to 2017, the agestandardized prevalence of RHD had a slight 3.0% (95% UI, 1.6 -4.3) increase, from 721.4 (95% UI, 688.7 -754.5) to 743.2 (95% UI, 709 -778.6) per 100 000 inhabitants, remaining higher in women than in men throughout the whole period (Table 5-1 and Chart 5-1.A). Although small for both sexes, the percent increase was numerically more pronounced in women (4.4%) than in men.…”
Section: Future Researchmentioning
confidence: 99%